Effects of Augmented Reality Learning Media on Students’ Cognitive Learning Outcomes in Virus Topics - Joice Elma Miranda Gulo; Wahyuningtyas, Riska Septia; Jendri Mamangkey (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
This study examines the effect of Augmented Reality (AR) media on students' cognitive learning outcomes on virus material in class X of SMA Negeri 51 Jakarta. The method used is a quasi-experimental method with a non-equivalent control group design, involving an experimental class with AR media and a control class with conventional media. Data were collected through pretests, posttests, and observation sheets to measure the implementation of learning and learning outcomes. The results of the analysis showed that AR media was implemented very well, with an average implementation of 97% during four meetings. The use of AR significantly improved students' cognitive learning outcomes in the domains of C1 (remembering), C2 (understanding), and C3 (applying) compared to conventional media. The results of the t-test showed a p value = 0.018 (p <0.05), with an average posttest of the experimental class of 73.08, higher than the control class of 65.63. AR media is effective in visualizing the abstract concept of viruses in improving students' understanding more deeply. The cognitive learning outcomes of students showed C1 = 82.14%, C2 = 81%, and C3 = 60%, higher than the control class. These results indicate that there is an influence of the use of Augmented reality media on students' cognitive learning outcomes on virus material at SMA Negeri 51 Jakarta.